Safety Feeling and Satisfaction Rates of Syrians Under Temporary Protection in Turkey's Eastern Province - Kaya, Ferit; Açık, Yasemin; Aktaş, Osman; Polat, Cahit; Kantarcıoğlu, Abdulkadir; Orak, Yavuz; Aktaş, Gonca (Ordu Üniversitesi, 2022)
Objective: This study aims to determine safety feeling and satisfaction rates of Syrians under temporary protection in an eastern province of Turkey.Methods: This study is a cross-sectional study. The study was conducted among Syrians under temporary protection over the age of 18 living in a province in the eastern Anatolian region of Turkey. Results: The average time of living of the Syrians in Turkey was 24.36 ± 15.46. 53.9% of the participants were women, and 46.1% were men. The average age of women was 37.18±11.59, while the average age of men was 37.59 ± 11.10. The average number of people staying at home was 6.95 ± 3.05. 69.6% of the participants in the study had a nuclear family structure. The ratio of disabled family members was 13.1%. 70.8% of those included in the study considers returning to Syria again. There was a positive correlation between the increase in family income and age and the average feeling of being safe. The average score of feeling safe was significantly higher in those who did not have the idea of returning to Syria.Conclusion: It has been observed that people do not have problems in accessing health services and the education of their children, but they have problems mostly due to language and economic difficulties.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi